2021
DOI: 10.1002/ajpa.24419
|View full text |Cite
|
Sign up to set email alerts
|

Age‐at‐death patterns and transition analysis trends for three Asian populations: Implications for [paleo]demography

Abstract: Objectives Age‐at‐death estimation provides biological anthropologists with fundamental biographic information to help resolve various theoretical and practical questions about both individual expression and populational trends in present and past contexts. Particularly, researchers interested in reconstructing past populations' mortality profiles have favored using Boldsen and colleagues' Transition Analysis (TA2), as the method provides both methodological and statistical solutions for optimally treating tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 79 publications
(130 reference statements)
0
3
0
Order By: Relevance
“…This claim has also been supported in previous validation experiments (e.g., Maaranen & Buckberry, 2018; Milner & Boldsen, 2012) for TA2, in which it appears that the accuracy of age estimation actually gets better after the 70‐year mark (with the most variability seen between the ages of 40 and 70). With the addition of new skeletal features in TA3, comparisons have shown that TA3 is even more precise in estimating both young adult (not overestimating) and old adult (not underestimating) age groups (also seen in previous TA iterations, e.g., Kim & Algee‐Hewitt, 2022; Lopez‐Cerquera & Casallas, 2018). On average, age interval lengths decreased from 34.2 years in TA2 to 17.2 years in TA3 (Getz, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…This claim has also been supported in previous validation experiments (e.g., Maaranen & Buckberry, 2018; Milner & Boldsen, 2012) for TA2, in which it appears that the accuracy of age estimation actually gets better after the 70‐year mark (with the most variability seen between the ages of 40 and 70). With the addition of new skeletal features in TA3, comparisons have shown that TA3 is even more precise in estimating both young adult (not overestimating) and old adult (not underestimating) age groups (also seen in previous TA iterations, e.g., Kim & Algee‐Hewitt, 2022; Lopez‐Cerquera & Casallas, 2018). On average, age interval lengths decreased from 34.2 years in TA2 to 17.2 years in TA3 (Getz, 2021).…”
Section: Discussionmentioning
confidence: 95%
“…While some error can be tolerated, we suggest that the use of the method presented here is paired with a discussion and acknowledgement of the age‐at‐death methods specifically used in accordance with this issue. Furthermore, given that some age‐at‐death estimation methods do produce reasonable results despite some error (Boldsen et al, 2002; Clark et al, 2020; Kim & Algee‐Hewitt, 2022; Milner & Boldsen, 2012), it is likely that certain methods may be better suited to this particular method upon further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Age estimates were generated via transition analysis using the Anthropological Database, Odense University (ADBOU) program Transition Analysis 2 (TA2), version 2.1.046 (Ousley et al, 2016). For each skeleton, pubic symphysis and auricular surface degeneration were scored alongside cranial suture obliteration (Kim & Algee‐Hewitt, 2022; Milner & Boldsen, 2012; Simon & Hubbe, 2021). This method generates a maximum likelihood point estimate (MLPE) for age‐at‐death, with a 95% confidence interval, from the scored pelvic and skull traits (Getz, 2020).…”
Section: Methodsmentioning
confidence: 99%